2012
DOI: 10.1002/pts.1971
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Sustainable Food Packaging Design

Abstract: The environmental impacts of packages have been found to be relatively small compared with the food items they contain. Furthermore, from the environmental and operational point of view, the most significant task of the package is to protect the product, which is important to acknowledge in the packaging design process. This study introduces a guiding framework for designing sustainable food packaging. In this approach, the entire life cycle of the product–package combination is taken into consideration. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 30 publications
0
126
0
9
Order By: Relevance
“…From the literature review, it was found that most plastic film assessments only considered one sustainability dimension [1,3,[24][25][26]; few considered two dimensions [27][28][29]; and very few considered three dimensions [30]. Academic and corporate interest in sustainable supply chain management has risen considerably in recent years [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the literature review, it was found that most plastic film assessments only considered one sustainability dimension [1,3,[24][25][26]; few considered two dimensions [27][28][29]; and very few considered three dimensions [30]. Academic and corporate interest in sustainable supply chain management has risen considerably in recent years [16].…”
Section: Resultsmentioning
confidence: 99%
“…Environmental calculations were based on carbon emissions, and economic calculations were based on costs. Grönman et al [28] presented a systematic framework for sustainable food packaging design using SWOT analysis and used the LCA method to evaluate the environmental and economic functions. Pires et al [29] considered sustainability criteria, which were aggregated using a multi-criteria decision making method on two dimensions: environmental aspects related to life cycle assessment and social aspects related to the environmental information on the packaging.…”
Section: Review Of Plastic Film Assessment Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparisons are made among packaging options, this point has to be borne in mind. Grönman et al (2013) has advocated a 'consideration of the properties of both the package and the product itself when designing the final package, in order to reduce both product losses and environmental impacts'. Azzi et al (2012) have written that the impact of packaging design on supply chain costs and performance can be devastating.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, environmental requirements have to be satisfied with productive and marketing needs [47], including also the clear separation between food macrocategories and related chemical concerns (different contamination episodes etc. ).…”
Section: Environmental Requirementsmentioning
confidence: 99%